The Relationship Between the Use of 3-Month DMPA Injectable Contraception and the Incidence of Spotting among Contraception Users - Ely Christiana Wahjuningtyas; Reny Retnaningsih (Health and Technology Journal (HTechJ), 2026)
The 3-month DMPA injectable contraceptive is widely used because of its effectiveness, convenience, and affordability. However, prolonged use may cause side effects, particularly menstrual disturbances such as spotting, which can affect user comfort and compliance. This study's aimed to analyze the association between the duration of 3-month DMPA injectable contraceptive use and the occurrence of spotting among family planning acceptors. This analytical cross-sectional study involved 30 family planning acceptors selected through purposive sampling. Data were collected using a structured questionnaire and analyzed using the Chi-square test with a significance level of 0.05. Among the 30 respondents, 66.7% had used the 3-month DMPA injectable contraceptive for 1–2 years, and 43.3% experienced spotting. Statistical analysis showed no significant association between the duration of 3-month DMPA use and spotting (p = 0.088). Spotting is a common side effect among users of the 3-month DMPA injectable contraceptive, but it is not significantly associated with the duration of use. Comprehensive counseling and education regarding potential side effects are essential to improve user comfort and contraceptive compliance.